Experimental parametric investigation of vapor ejector for refrigeration applications. (1st November 2018) - Poirier, Michel; Giguère, Daniel; Sapoundjiev, Hristo
Abstract: A prototype ejector system having a nominal cooling capacity of 30 kW was used to study the influence of ejector geometry and operating conditions on the ejector performance. Experiments were realized over a wide parameter range: primary inlet pressure from 1700 to 2900 kPa; secondary inlet pressure from 170 to 550 kPa; outlet pressure from 350 to 1000 kPa. The performance was evaluated in terms of the entrainment ratio and the temperature lift. The experimental results led to the following observations: (a) A simple calculation of the primary mass flow rate can be used for the design of ejector systems; (b) A given ejector operated at fixed primary inlet pressure shows a range of outlet pressures where the entrainment ratio is maximum. A correlation of the optimal entrainment ratio versus the primary pressure is proposed; (c) There is an inverse relationship between the temperature lift and the entrainment ratio; (d) For a fixed primary inlet pressure, the optimal outlet pressure can be set at a given value by the appropriate geometry of the ejector. Finally, a two-plateau behavior of entrainment ratio as a function of outlet pressure was observed, which might be related to an improper nozzle exit position. Highlights: Simple approach to calculate the primary mass flow rate. Impact of the primary pressure on the critical outlet pressure. Inverse relationship between the temperature lift and the entrainment ratio. Influence of the ratio of mixing section area over the primary nozzle throat area.